Targeting irradiation‐induced mitogen‐activated protein kinase activation in vitro and in an ex vivo model for human head and neck cancer. (26th February 2016) - Affolter, Annette; Muller, Marie‐France; Sommer, Katharina; Stenzinger, Albrecht; Zaoui, Karim; Lorenz, Katja; Wolf, Thomas; Sharma, Sarika; Wolf, Janina; Perner, Sven; Weber, Klaus‐Josef; Freier, Kolja; et al.
Abstract: Background: Despite new radiotherapeutic strategies, radioresistance in head and neck squamous cell carcinoma (HNSCC) remains a major problem. Preclinical model systems are needed to identify resistance mechanisms in this heterogeneous entity. Methods: We elucidated the interplay among mitogen‐activated protein kinase (MAPK)‐inhibition, radiation, and p53 mutations in vitro and in a novel ex vivo model derived from vital human HNSCC samples. HNSCC cell lines (p53WT/mut) were treated with the mitogen‐activated protein kinase (MEK)‐inhibitor PD‐0325901 and subsequently irradiated. Radiosensitization was functionally assessed and evaluated in the ex vivo model. Results: We observed a pronounced irradiation‐induced extracellular signal‐regulated kinase (ERK) phosphorylation in 2 cell lines, which was independent of their p53 mutation status and associated with PD‐0325901‐related radiosensitization in a clonogenic assay. Heterogeneity in irradiation‐induced ERK phosphorylation and in radiosensitization after MEK‐inhibition was also reflected in the ex vivo model. Conclusion: We provide experimental evidence for radiosensitizing effects of PD‐0325901 in HNSCC. The ex vivo culture technology might offer a promising tool for individualized drug efficacy testing. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2049–E2061, 2016